2020
DOI: 10.1038/s41537-020-0104-x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent cannabis use as an independent risk factor for violent behaviors in patients with schizophrenia

Abstract: Although recent studies have shown a moderately strong association between cannabis use and violence among people with severe mental disorders, the direction of this association has not been investigated prospectively in a population with schizophrenia. Therefore, this study aims to determine, using cross-lag models, whether a temporal relationship between cumulative cannabis use and violence exists in a population with schizophrenia. The authors reported findings covering an 18month period from a randomized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
1
10
0
1
Order By: Relevance
“…Results remained significant after controlling for alcohol and stimulant use. As such, this analysis of longitudinal data showed a unidirectional association between cannabis and violence in schizophrenia (109). On the other hand, our study on adolescents also supported a reverse relationship, that is that externalizing behavior in youths may lead to the subsequent use of cannabis.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Results remained significant after controlling for alcohol and stimulant use. As such, this analysis of longitudinal data showed a unidirectional association between cannabis and violence in schizophrenia (109). On the other hand, our study on adolescents also supported a reverse relationship, that is that externalizing behavior in youths may lead to the subsequent use of cannabis.…”
Section: Discussionsupporting
confidence: 77%
“…Beyond associational research, our studies using longitudinal designs were conducted in the aim to further understand the direction of the cannabis-violence association as solely few investigations have been carried out on the matter (27,31,33,(107)(108)(109)(110). Our studies on psychiatric samples have supported the finding of a unidirectional association between cannabis use and violence (108,109). In this regard, our research team has recently re-analyzed data from the NIHMfunded CATIE trial.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For example, in a birth cohort study, schizophrenic patients with CU have been found to be 3.8 times more likely to be violent than control subjects ( 3 ). A recent longitudinal study ( 57 ) of 965 patients showed that persistent CU induces subsequent VB, after controlling for stimulants and alcohol use.…”
Section: Cannabis Use and Violent Behavior In The Early Phase Of Psyc...mentioning
confidence: 99%
“…Het blijkt bijvoorbeeld dat cannabisgebruik pijn kan verlichten, ontspannend kan werken en positieve gevoelens kan geven (Green et al, 2003), terwijl het bij iemand met schizofrenie vanwege de hallucinerende werking tot psychotische ontregeling en gewelddadig gedrag kan leiden (Beaudoin et al, 2020). Er blijken dus verschillende routes mogelijk waarop middelengebruik zich tot crimineel gedrag kan verhouden waar een recent literatuuroverzicht voor nodig is.…”
Section: Tbs En Onderzoek Naar Middelengebruik En Crimineel Gedragunclassified